Novel hormonal agents for metastatic Castration-Resistant Prostate Cancer: comparing outcomes. A single-center retrospective study - Jarimba, Roberto Saldanha (2021)
Prostate cancer is the most common cancer in men, accounting for 15% of all diagnosed cancers and is the sixth leading cause of cancerrelated deaths amongst men worldwide. Abiraterone and enzalutamide were the first two novel hormonal agents approved for the treatment of metastatic prostate cancer but there is a lack of quality evidence regarding which is associated with better outcomes and who would benefit the most with one or another of these drugs.